Crataegus Aronia protects and reverses vascular inflammation in a high fat diet rat model by an antioxidant mechanism and modulating serum levels of oxidized low-density lipoprotein - Abdullah S. Shatoor; Suliman Al Humayed; Mahmoud A. Alkhateeb; Khalid A. Shatoor; Hussain Aldera; Mohammed Alassiri; Ali A. Shati (Taylor & Francis Group, 2019)
Context: Crataegus aronia (Willd.) Bosc (Rosaceae) (syn. Azarolus L) is traditionally used to treat cardiovascular disorders. Objectives: To investigate C. aronia protection against a high-fat diet (HFD)-induced vascular inflammation in rats. Materials and methods: Wistar Male rats (180-220 g) were divided (n = 10/group) as control fed a standard diet (STD), STD + C. aronia (200 mg/kg, orally), HFD, HFD + C. aronia and HFD post-treated with C. aronia. Simvastatin (20 mg/kg) was co- or post-administered as a positive control drug. HFD was given for 8 weeks, and all other treatments were administered for 4 weeks. Results: Most significantly, co-administration of C. aronia to HFD-fed rats reduced the thickness of aorta tunica media (90 ± 5 vs. 160 ± 11.3 µm) and adventitia (54.3 ± 3.8 vs. 93.6 ± 9.4 µm). It also lowered protein levels of TNF-α (0.51 ± 0.15 and 0.15 ± 0.16 vs. 0.1 ± 0.09%) and IL-6 (0.52 ± 0.19 vs. 1.0 ± 0.2%) in their aorta or serum (5.9 ± 0.91 vs. 12.98 ± 1.3 ng/mL and 78.1 ± 6.7 vs. 439 ± 78 pg/mL, respectively). It also lowered all serum lipids and increased aorta levels of GSH levels (70.4 ± 4.0 vs. 40.7 µM) and activity of SOD (5.7 ± 0.7 vs. 2.9 ± 0.6 U/mg) and decreased serum levels of ox-LDL-c (566.7 ± 46 vs. 1817 ± 147 ng/mL). Such effects were more profound than all other treatments. Conclusions: C. aronia inhibits the HFD-induced vascular inflammation and its use in clinical trials is recommended.